RELASI STAKEHOLDER KEPARIWISATAAN DALAM UPAYA BERTAHAN DI TENGAH PANDEMI COVID-19: - Ni Nyoman Citta Maya Dewi; Ida Ayu Tary Puspa; I Gede Januariawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The Covid-19 pandemic has lasted for more than two years and has had a significant impact on Bali's tourism and economy. The phenomenon of the Covid-19 pandemic and efforts to survive by tourism stakeholders in Bali have not escaped media interference. The focus of this research is to analyze tourism stakeholder relations in Badung and Denpasar in an effort to survive in the Covid-19 pandemic based on the Bali Post mass media framing analysis. With descriptive qualitative research, the results of the analysis using the Robert N. Entmant framing model method are written in narrative form. After being analyzed using the framing method, then each problem formulation is dissected with the social construction theory of mass media, organizational control theory and agenda setting theory, as well as framing theory. As a result, power relations are obtained from the government to tourism actors in the tourism and media industries. This power relationship is asymmetrical from the government to tourism actors. In this effort to survive, obstacles were also found, especially personal barriers such as emotions, prejudices, and biases from tourism actors to the government, causing conflict. However, with the theory of organizational control carried out by the government, the implication is to create a conducive and orderly atmosphere among tourism actors. There are two efforts found, namely technical and non-technical efforts. These efforts have made tourism actors able to survive in the Covid-19 pandemic.